The Effect of Board Composition and Managerial Pay on Saudi Firm Performance - Mamdouh Abdulaziz Saleh Al-Faryan (Review of Quantitative Finance and Accounting, 2021)
Using five empirical methodologies to account for endogeneity issues, this study investigates the effects of board independence and managerial pay on the performance of 169 Saudi listed firms between 2007 and the end of 2014. Studying board independence and managerial pay utilises the main internal governance mechanism in relation to firm performance; therefore, the effect of the 2009 exogenous regulatory shock on board independence was also examined to learn whether it impacted firm performance. The empirical results show that the board composition–performance relationship is endogenous. Strong evidence is found through the dynamic generalised method of moments estimation, which indicates that board composition has a positive relationship with return on assets, and poor past performance of listed firms has a negative impact on the current level of performance. The difference-in-differences approach results show a positive relationship between board composition, stock returns, and Tobin's Q. The findings also reveal that managerial pay has a positive relationship with firm performance, although when endogeneity is considered, there is a smaller positive relationship and a decrease in significance levels. Thus, pay-for-performance in Saudi Arabia matters, and firms are not simply controlled by the government. The results of this study have implications for both policy makers and investors. In particular, policy makers and Saudi regulators can evaluate the impact of Saudi corporate governance arrangements and, in so doing, highlight changes in corporate governance arrangements that need to be made to achieve their economic objectives, such as Vision 2030. This study also contributes to the literature by showing the importance of considering endogeneity in studies.
Keywords: G30; G34; G38; J33; K22; L25; 330; Board composition; Managerial pay; Firm performance; Endogeneity; Corporate governance; Saudi Arabia